Influencing factors of patient safety in anesthesia services in a low- and middle-income country - Heriwardito, Aldy; Ramlan, Andi Ade Wijaya; Zahra, Raihanita; Martira, Amelia; Pramodana, Bintang; Bintartho, Agung; Sukmono, Raden Besthadi; Lasanudin, Joshua Eldad Frederich (Intelektual Pustaka Media Utama, 2025)
Patient safety in anesthesia remains a concern in low- and middle-income countries due to workforce shortages, limited equipment, and inconsistent protocols. In Jakarta, where demand for anesthesia is rising, baseline data on these parameters are lacking. This study aimed to identify gaps in human resources, equipment availability, and safety protocol adherence. A cross-sectional survey of all actively practicing anesthesiologists in Jakarta was conducted in January 2024, yielding 115 responses. The questionnaire, developed and face-validated through a focus group with senior anesthesiologists, covered three domains: human resources, facilities and equipment, and protocols. Internal reliability was assessed using Cronbach’s alpha. Participation was voluntary, responses were anonymous, and data were analyzed using descriptive statistics. Prolonged work hours were reported by a minority of respondents (6.1-7%), with 22.7% agreeing that anesthesiologists' workload is too high. Most rated human resource parameters positively (median 4/5), but access to basic monitoring devices for oxygenation, ventilation, circulation, and temperature was limited. Protocol adherence was generally high (median 4-5/5), though a small minority of institutions lacked incident reporting pathways, patient risk assessment, and post-surgical recovery rooms. Improving patient safety in Jakarta requires ensuring essential monitoring equipment, optimizing staffing to manage workload, and mandating full perioperative safety protocols across facilities.